Perceived discrimination and subjective well-being among Middle Eastern migrants in Australia: The moderating role of perceived social support. (March 2021) - Hashemi, Neda; Marzban, Maryam; Sebar, Bernadette; Harris, Neil
Background: Middle Eastern (ME) migrants are vulnerable to developing mental health problems due to pre-migration and post-migration traumas and stresses. The evidence on the subjective well-being of ME migrants and its contributing factors is limited and inconclusive. Objectives: The aim of this study is to examine the moderating role of perceived social support in the association between perceived discrimination and subjective well-being, after controlling for socio-demographic factors. Method(s): This cross-sectional survey study was conducted in Queensland, Australia. A total of 382 first-generation young adult ME migrants, aged between 20 to 39 years, completed a self-administered questionnaire. To analyse data, a series of three hierarchical multiple regression (HMR) analyses were conducted, one for each of the subjective well-being components (i.e., positive affect, negative affect, and satisfaction with life). The interaction between perceived social support and perceived discrimination for the prediction of subjective well-being components was further explored using simple slope analysis. Results: Gender was found to be a significant predictor of positive and negative affect. Education was found to predict satisfaction with life, but not positive and negative affect. Married migrants were found to have significantly higher life satisfaction, positive affect and lower negative affect. Perceived social support had a moderating role in the association between perceived discrimination and subjective well-being. Conclusion: Considering the buffering role of perceived social support against the adverse effects of perceived discrimination on subjective well-being, organizations and individuals working with ME migrants should acknowledge the significance of social support and improve their capacity to deliver effective and appropriate social support services to migrants experiencing discrimination.